1984
DOI: 10.1159/000457142
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay of Vasotocin, Vasopressin, and Oxytocin in Human Neonatal Cerebrospinal and Amniotic Fluid

Abstract: Arginine vasotocin (AVT) has been measured in neonatal cerebrospinal fluid (CSF) and human amniotic fluid using a newly developed specific radioimmunoassay system. There were significant amounts of AVT in all samples. Vasopressin and oxytocin also were measured in the samples and could not account for the levels of vasotocin found. The source and function of these neurohypophyseal peptides in CSF and amniotic fluid remains speculative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…4) degradation (with cystineaminopeptidase of human pregnancy plasma or with trypsin) abolished immunoreactivity (data not shown). In addition, none of the antisera cross-react significantly with either the ring of OT (tocinamide [18]) or the tripeptide tail portion of AVP (18). Thus from the data in Table I, the irAVT observed in the present studies of ovine fetal plasma, urine, and amniotic fluid does not appear to be attributable to any of the known neurohypophysial hormones except AVT or to known degradation products.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…4) degradation (with cystineaminopeptidase of human pregnancy plasma or with trypsin) abolished immunoreactivity (data not shown). In addition, none of the antisera cross-react significantly with either the ring of OT (tocinamide [18]) or the tripeptide tail portion of AVP (18). Thus from the data in Table I, the irAVT observed in the present studies of ovine fetal plasma, urine, and amniotic fluid does not appear to be attributable to any of the known neurohypophysial hormones except AVT or to known degradation products.…”
Section: Discussionmentioning
confidence: 45%
“…In studies using both RIA and HPLC methodology, AVT recently has been identified in the neurohypophysis of mid-term human fetuses (24). Although AVT has also been reported in human newborn cerebrospinal fluid (18,25), the presence of AVT in mammalian circulation has not been investigated. In this study highly sensitive RIA and HPLC-RIA systems were used in the quantification and characterization of irAVT in various biological fluids of fetal sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the cross-reac tivity of the AVT, AVP and OT antisera has been extensively characterized [1,5,8] the RIA data alone indicate that neither the AVT nor the OT-VT immunoreactivity can be attributed to any of the other known neu rohypophysial hormones or any known me tabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Radioimmunoassays for AVT, AVP and OT con centrations were performed using three antisera, R-4 [8], R-357 [9], and R-421 [6], developed in New Zea land white rabbits. The cross-reaction of these anti sera with a variety of potential reactants [5,7] and the basic assay procedures employed have been described in detail [5].…”
Section: Radioimmunoassaymentioning
confidence: 99%